Factores que generan el absentismo escolar en los estudiantes del 1° "G" de la institución educativa Francisco Lizarzaburu del distrito "El Porvenir" - ciudad de Trujillo, durante el año 2016. - Alva Mostacero, Viviana Jhaneth (2017)
This research was carried out at the Francisco Lizarzaburu Educational Institution of the El Porvenir district, with the purpose of identifying the factors of School Absenteeism in the freshmen of secondary school, section "G". Likewise, the sample consisted of 31 students, with ages ranging from 12 to 17 years, male and female. The investigation of explanatory character, allowed to obtain results on the problematic one based on quantitative and qualitative data, making use of the deductive, inductive, descriptico, and statistical methods. Two instruments were used: the Rosenberg Scale of Self-esteem and the Evaluation Scale of the Life Project of Ortega de la Cuesta y Díaz, the last one modified by the authors Mostacero Nureña Eliana and Paredes Silvestre Pamela. Finally it is announced that the factors that generate School Absenteeism in the students of the 1st "G" of the Francisco Lizarzaburu Educational Institution of the "El Porvenir" district, are Low Self-esteem, not feeling able to achieve what they want or simply do not have the motivation to do so, since he considers that he does not have enough skills and abilities to respond to studies. On the other hand, the Absence of a Life Project, not considering goals in the short, medium and long term, considering other activities such as household chores, support in family economic activities, all of which leads students to lose interest. for the study, since they see it as a secondary activity, and therefore have frequent faults to the educational system.